IMPLEMENTASI FUNGSI SOSIAL LEMBAGA KEUANGAN SYARIAH SEBAGAI KEWAJIBAN HUKUM DALAM MEWUJUDKAN KEADILAN - Ahmad Rifat Mathar; Ai Rahmawati; Nuraida Fitriani (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2025)
Abstract--Islamic financial institutions (IFIs) exist as institutions that not only perform financial intermediation functions, similar to conventional financial institutions, but also uphold social responsibility within the framework of justice and equitable welfare inherent in Islamic values and the implementation of Maqasid al-Shariah. In the context of Indonesia's dual economic system, Islamic Financial Institutions possess distinct characteristics compared to conventional financial institutions, particularly in the management of social funds such as zakat, infaq, and sadaqah. This research examines the social function of Islamic financial institutions as a legal obligation stipulated in laws and regulations, specifically Law Number 21 of 2008 concerning Islamic Banking and Financial Services Authority (OJK) Regulation Number 51/POJK.03/2017 concerning the Implementation of Sustainable Finance for Financial Services Institutions, Issuers, and Public Companies. One concrete form of this social function is the management of social funds such as zakat, infaq, sadaqah, and waqf, including funds that cannot be recognized as income (TBDSP). These are funds originating from transactions not in accordance with Shariah principles, such as interest from conventional current accounts or other non-halal income. These TBDSP funds must be channeled for social purposes and cannot be utilized as institutional profit. This research was conducted using an approach based on the theories of wealth distribution and social justice in Islam, by examining the 2024 annual reports of the three largest Islamic financial institutions with the highest assets in Indonesia: Bank Syariah Indonesia (BSI), Bank Syariah Muamalat Indonesia (BMI), and Bank CIMB Niaga Syariah. The analysis results indicate that Islamic Financial Institutions have implemented their social functions through the active management and distribution of social funds, as part of their moral responsibility and Shariah mandate to create distributive justice and the welfare of the ummah.